2018
DOI: 10.1002/2017je005255
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Rocket Dust Storms on Mars in the LMD Martian GCM: Modeling Details and Validation

Abstract: The origin of the detached dust layers observed by the Mars Climate Sounder aboard the Mars Reconnaissance Orbiter is still debated. Spiga et al. (2013, https://doi.org/10.1002/jgre.20046) revealed that deep mesoscale convective “rocket dust storms” are likely to play an important role in forming these dust layers. To investigate how the detached dust layers are generated by this mesoscale phenomenon and subsequently evolve at larger scales, a parameterization of rocket dust storms to represent the mesoscale d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 48 publications
0
43
0
2
Order By: Relevance
“…Detached dust layers were previously identified on many occasions [14][15][16] , and their existence has been explained by uplifting during strong convection processes [17][18][19][20] . Water ice clouds may be responsible for some of the observed layers, as indicated by observations at other wavelengths and by previous investigations [21][22][23] .…”
mentioning
confidence: 99%
“…Detached dust layers were previously identified on many occasions [14][15][16] , and their existence has been explained by uplifting during strong convection processes [17][18][19][20] . Water ice clouds may be responsible for some of the observed layers, as indicated by observations at other wavelengths and by previous investigations [21][22][23] .…”
mentioning
confidence: 99%
“…Simulations suggested that thermal tides can enhance the net meridional transport of aerosols through momentum flux divergence via tidal dissipation 46 . According to recent observational and numerical studies, the dusty deep convection becomes more widespread in the mid-latitudes under dust storm conditions 45,47 . It should be noted that in the period from noon to the early afternoon, when dusty deep convection is expected to be the strongest, the water vapor is retreating to higher latitudes from the equatorial region ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that there are missing processes in the GCM that relate to daytime activity, e.g. sub grid-scale deep convective events that are currently not represented in the model [Spiga et al, 2013;Daerden et al, 2015;Wang et al, 2018;Heavens et al, 2018]. To impose control over the vertical profile, we use a prescribed distribution based on Conrath [1975] (also see Montmessin et al, [2004] for the equations).…”
Section: Model and Scenario Descriptionmentioning
confidence: 99%
“…This layer is difficult to implement using a simple Conrath description and was not considered in our simulations. In reality it may be caused by non-local deep convective events when the GDS develops [Spiga et al, 2013;Wang et al, 2018;Heavens et al, 2018].…”
Section: Comparing Model Simulations and Nomad Observationsmentioning
confidence: 99%